Conexão com a natureza, percepção ambiental e práticas pedagógicas de professoras/es em escolas de Alta Floresta - MT - Santos, Clara Machado dos (2020)
This research project is the result of a partnership between the Univesidade Federal de São Carlos (UFSCar) and the Instituto Ouro Verde (IOV), in the municipality of Alta Floresta, in the very north of the State of Mato Grosso, in the Arc of Deforestation, in which the following were researched: a Community School located in a peri-urban area that employs a mix of innovative pedagogical approaches and a State School located in a rural settlement that uses traditional pedagogy. The general objective of the study was to analyze the connection, environmental perception and the pedagogical practices of the teachers, in order to better understand the diversity of actions and views of the teachers regarding Environmental Education in the rural context. The methodological procedures were based on a qualitative approach, that were developed in stages in the approximation of the study context and fieldwork through observation of meetings, semi-structured interviews with ten teachers and use of field journals. In the data analysis and interpretation stage were used Iramuteq software (for textual corpus analysis) and ATLAS.ti software, which supported the analysis of thematic categorical content. The research process was conducted with full consideration of ethics. The results of the study show the teachers of both schools displayed interest in and a connection with nature, as well as a significant feeling of belonging and identity with the place they live. The State School was characterized as a rural school and the Community School as a countryside school. The countryside was identified as an environment of innumerable potentialities. The attitudes of the teachers of the State School stood out, particularly: questioning, reflection, a holistic view and concern regarding integrating the value of people of the countryside into classroom work. Were observed differences in environmental educational practices, insofar as the Community School values and enables permanent practices that are based on interaction with the community, through the involvement of families. The State School displayed particular practices in environmental education due to turnover of the teaching staff and discontinuity of practices, and the fragility in the process of planning, structuring and communicating the Political Pedagogical Project to the teaching staff. However, the State School teachers expressed interest in a transversal approach and a reflective and dialogical praxis. By bringing together the teachers' interests, research development and the state and municipality's involvement in promoting and maintaining public policies aimed at countryside education and the continued education of education professionals, a significant contribution can be made to local and regional sustainable development.